Satisfaction and Improvements in Peritoneal Dialysis Outcomes Associated with Telehealth - Magnus, Manya; Sikka, Neal; Cherian, Teena; Lew, Susie Q. (Applied Clinical Informatics, 2017)
Background and Significance: End stage renal disease (ESRD) affects approximately 660,000 persons in the US each year, representing a significant financial burden to the health care system and affected individuals. Telehealth approaches to care offer an important means of reducing costs as well as increasing autonomy for patients. Understanding patient satisfaction with telehealth provides a key towards eventual scalability.Materials and Methods: Quarterly surveys were conducted to characterize satisfaction with remote biometric monitoring (RBM) for blood pressure, weight, glucose and peritoneal dialysis (PD)-specific educational online videos for ESRD patients using PD.Results: Of 300 participants, 67% participated in the surveys and provided baseline and at least one follow-up assessment. The majority were 45 to 64 years of age (50.5%), Black (64.5%), married or living with significant other (52.0%), and had more than a high school degree (73.0%). RBM was associated with perceived autonomy and confidence in health care activities and decreased negative perceptions of PD care and ESRD. The majority of participants (80.1%) indicated that they were satisfied or completely satisfied with the system. Participants found that the interface increased confidence, reduced frustration, and related perceptions were significantly and positively altered (p<0.05) for each of the separate telehealth components. Educational videos were well utilized with nearly half of the participants (42.5%) reporting that they watched at least one of the videos, and the majority reporting that the videos seen had an overall positive impact on health. Discussion and Conclusions: Supplementing PD with telehealth has the potential to have a positive impact on patient perceptions of PD care and consequently improve clinical outcomes.
Keywords: Chronic kidney failure; peritoneal dialysis; telemedicine; tele-education; patient satisfaction; patient outcome assessment; telehealth; end stage renal disease; remote biometric monitoring